MANAJEMEN KEUNGAN YAYASAN AL ISHLAH DALAM PENINGKATAN MUTU TPA AL ISHLAH DESA SRIBASUKI KECAMATAN BATANGHARI LAMPUNG TIMUR - Imron; Syahrul (Journal Tafkirul Iqtishodiyyah, 2024)
The Al Ishlah Foundation, which is located in Sribasuki Village, Batanghari, East Lampung, plays a very important role in instilling moral values in children in the surrounding environment. This institution develops Al-Qur'an Education Park (TPA) education as part of Islamic education. This research uses a descriptive qualitative approach to explore the financial management of the Al Ishlah Foundation. The foundation's funding sources come from single donors and non-permanent donors. In managing its finances, the foundation prepares an Income and Expenditure Budget Plan (RAPB) which includes a revenue budget from donors as well as an expenditure budget for routine and non-routine needs. Financial management activities carried out include receiving funds from donors and disbursing funds to fund various activities. In addition, financial reports are prepared every month. The reporting process includes financial recording carried out by the foundation treasurer, collecting revenue and expenditure data into the Foundation Activity Report format. This report is then submitted every month to the chairman of the board of the Al Ishlah Foundation in Sribasuki Village, Batanghari, East Lampung.